Oxford Research Encyclopedia of Criminology and Criminal Justice 2017
DOI: 10.1093/acrefore/9780190264079.013.14
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Bullying in School and Work Contexts

Abstract: The knowledge base on bullying within school and working contexts has matured to the extent that researchers and practitioners are developing a deeper understanding of this complex social relationship problem. Although controversies still exist, evidence to date provides estimates of the prevalence of bullying, risk factors for bullying, antecedents of bullying, and theoretical models explaining bullying behavior and experience. There is little doubt that bullying in all its forms can have severe negative impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…With a reported global prevalence fluctuating between 11% and 18% [ 7 ], workplace bullying has become a considerable problem in contemporary working life as well as a prominent issue in occupational health [ 8 ]. More specifically, previous research has shown that workplace bullying is wide-spread particularly in the academic context [ 9 , 10 ]. Teachers are at increased risk of being exposed to bullying by colleagues in comparison to other type of employees [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With a reported global prevalence fluctuating between 11% and 18% [ 7 ], workplace bullying has become a considerable problem in contemporary working life as well as a prominent issue in occupational health [ 8 ]. More specifically, previous research has shown that workplace bullying is wide-spread particularly in the academic context [ 9 , 10 ]. Teachers are at increased risk of being exposed to bullying by colleagues in comparison to other type of employees [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%